Evolution of Paget's disease of bone in adults inheriting SQSTM1 mutations. (6th March 2015) - Cundy, Tim; Rutland, Michael D.; Naot, Dorit; Bolland, Mark
Summary Context The cause of Paget's disease of bone (PDB) is unknown, but genetic factors, particularly SQSTM1 mutations, and environmental factors are important. Objective To investigate the development of PDB in asymptomatic relatives carrying SQSTM1 mutations to determine whether a secular trend towards a less severe phenotype is evident, and to estimate prospectively the rate at which PDB emerged in this genetically susceptible population. Design We recruited first‐degree relatives of patients with PDB [33 adult offspring (mean age 45) and 1 sibling] with a familial SQSTM1 mutation. We determined the presence of PDB with skeletal scintiscans and confirmatory radiographs. Those negative for PDB on the initial scan were investigated again a mean 5·1 years later. Results The initial skeletal scintiscan demonstrated PDB in six subjects; 26 of the remaining 28 unaffected subjects had a second scintiscan, with two new cases of monostotic PDB diagnosed in 134 patient‐years of follow‐up. In the total eight adult offspring diagnosed with PDB, the age of diagnosis was greater, by at least 10 years, than that in the 21 probands with clinically identified PDB (P = 0·005). In adult offspring who were older at the time of skeletal scintigraphy than their affected parents were at the time of clinical diagnosis, the difference was even more marked (P < 0·001). In adult offspring with PDB, the disease was significantly less extensive than in their affected parent, as judged by alkaline phosphatase and disease extent (P < 0·003). Conclusion These findings suggest a substantial gene–environment interaction: the emergence of PDB in offspring inheriting SQSTM1 mutations is delayed by at least a decade, has a substantially attenuated phenotype and occurs at a low rate between the (mean) ages of 45 and 50 years. The nature of the environmental factor is unknown.